Pengaruh Jaminan Sosial Terhadap Produktivitas Kerja Karyawan Pada PT. Asrindo Citraseni Satria Balai Makam Kec. Mandau Kab. Bengkalis Riau - Wahyu Azhar Ritonga; Junaidi Mustapa Harahap; Shabrina Rasyid Munthe; Eko Firman Susilo; Jupriaman Jupriaman; Sangkot Idris Ritonga (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2022)
Analyzing the effect of social security on performance productivity, the most dominant factor on employee performance productivity at PT. Asrindo Citraseni Satria Cemetery Hall Kec. Mandau District. Bengkalis Riau. The population in this study was 263 people. The analytical method used is descriptive analysis method and simple linear regression analysis method. This type of research is associative research, and the data used are primary data and secondary data obtained through a study of documentation and a list of statements which are measured using a Likert scale. The data was statistically processed with the SPSS 20.0 for windows program, namely the t test model and the determinant coefficient (R2). The results of this study indicate that simultaneously social security has a positive and significant effect on the productivity of employee performance at PT. Asrindo Citraseni Satria Balai Makam, social security has a positive and significant partial effect on productivity performance. Based on simple linear regression processing, the results of simple linear regression are obtained as follows: Y = 3.077 + 0.810X, from the figures obtained, the level of social security obtained is 3.077, which means that there is a positive relationship between social security, performance productivity will still have a regression coefficient of X of 0.810 means that for every one unit increase in the social security variable, the productivity of performance will increase by 0.810 units. R Square of 0.677 means 67.7% of performance productivity at PT. Asrindo Citraseni Satria Cemetery Hall Kec. Mandau District. Bengkalis Riau can be explained by variations in social security and the remaining 33.2% can be explained by other factors not examined in this study.